Message to complementary and alternative medicine: evidence is a better friend than power - Vickers, Andrew J (BioMed Central, 2001)
BACKGROUND: Evidence-based medicine (EBM) is being embraced by an increasing number of practitioners and advocates of complementary and alternative medicine (CAM). A significant constituency within CAM, however, appears to have substantive doubts about EBM and some are expressly hostile. DISCUSSION: Many of the arguments raised against EBM within the CAM community are based on a caricature radically at odds with established, accepted and published principles of EBM practice. Contrary to what has sometimes been argued, EBM is not cookbook medicine that ignores individual needs. Neither does EBM mandate that only proven therapies should be used. Before EBM, decisions on health care tended to be based on tradition, power and influence. Such modes usually act to the disadvantage of marginal groups. CONCLUSION: By placing CAM on an equal footing with conventional medicine - what matters for both is evidence of effectiveness - EBM provides an opportunity for CAM to find an appropriate and just place in health care.